High global satisfaction in magnetically controlled elongations in 29 early-onset scoliosis patients versus primary spinal fusion in 20 adolescent idiopathic scoliosis patients - Simon T Skov; Cody Bünger; Jan D Rölfing; Ebbe S Hansen; Kristian Høy; Kestutis Valancius; Peter Helmig; Haisheng Li (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2019)
Background and purpose: Early-Onset Scoliosis (EOS) treatment aim to improve natural history and the child's quality of life. Magnetically Controlled Growing-Rods (MCGRs) represented a major evolution in distraction-based management of EOS by eliminating the surgical elongations. The technique can be used until cessation of growth and consequently it overlaps with primary Permanent Deformity Surgery (PDS). Patient reported outcomes of growth instrumentation compared to PDS is an interesting but uninvestigated subject. Our aim was to investigate the psychological burden, physical burden and global satisfaction in MCGR lengthening procedures in EOS patients and their parents, compared to PDS in adolescent idiopathic scoliosis patients. Patients and methods: A single-center cross-sectional cohort study: 29 MCGR-treated EOS patients, mean age 11(range, 6-14) years, compared to a PDS control group of 20 AIS patients age 16(12-20) years. Follow up in the MCGR group was 25(SD 14) months and 19(SD 12) months in the PDS group. The parents responded to a 9-item Satisfaction Questionnaire with a 0-10 Likert scale [0 none, 10 maximum].  Results: The median (range) physical strain was 0(0-7) for MCGR vs. 7(5-9) in PDS, the psychological strain was 0(0-7) vs. 7(0-10), the procedure related back pain was 0(0-5) vs. 8(0-10), the pain intensity between distractions/follow-up 0(0-8) vs. 2(0-8), the parental concern was 0(0-7) vs. 9(2-10). Overall satisfaction of the treatment concept was 10(6-10) vs. 9(2-10).  Interpretation: Overall satisfaction was uniformly high in both groups. Both the physical and psychological strain and pain in conjunction with MCGR lengthening procedures were low in comparison with primary deformity surgery. Level of evidence: Level IV, cross-sectional cohort study.